Administratorsâ Roles in Training Programs and Their Relationship with Traineesâ Motivation - Ismail, Azman; Abdullah, Anis Anisah; Mohd Soffian Lee, Umi Hamidaton; Mohamad, Nur Izzaty; Ibrahim, Nurul Inani (Binus Business Review, 2018)
This research was conducted to assess the relationship between the role of administrators in training programs and the motivation level of the trainees. The data were collected through a survey method conducted on employees at a government agency in East Malaysia. The outcomes of SmartPLS path model analysis show three important findings. First, administratorsâ roles in training programs are significantly related to traineesâ motivation. Second, provision of support is significantly linked to the motivation of the trainees. Third, communication is significantly related to the motivation level of the trainees. Thus, the findings indicate that administratorsâ roles, support, and communication act as significant determinants of traineesâ motivation in an organizational sample.